Rosmarinic acid and zinc ion double-crosslinking PVA composite film as well as preparation method and application thereof
Through the preparation method of rosemary acid and zinc ion double crosslinked PVA composite film, the problem of insufficient antibacterial, antioxidant and ultraviolet resistance of polyvinyl alcohol films is solved, and higher food shelf life and sensory characteristics are achieved.
Patent Information
- Application Number
- CN202411577133.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing polyvinyl alcohol (PVA) food packaging film has low antibacterial, antioxidant and ultraviolet resistance, making it difficult to extend the shelf life of food and improve sensory characteristics.
The preparation method of rosemary acid and zinc ion double crosslinked PVA composite film is adopted. Rosmarinic acid and zinc ion double crosslinked composite film is formed by mixing and reacting rosemary acid with aqueous polyvinyl alcohol solution, and dialysis and mixing with zinc chloride solution.
It significantly improves the antibacterial, antioxidant and ultraviolet resistance of polyvinyl alcohol films, while improving the mechanical properties of the film, extending the shelf life of food and improving sensory characteristics.
Smart Images

Figure CN119552394A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyvinyl alcohol composite film preparation, and in particular to a rosmarinic acid and zinc ion double-crosslinked PVA composite film and a preparation method and application thereof. Background Art
[0002] Polyvinyl alcohol (PVA) is a hydrophilic semi-crystalline polymer used in food packaging films. However, its antibacterial, antioxidant and UV resistance are relatively low. It is of great significance to improve the antibacterial, antioxidant and UV resistance of food packaging films made of polyvinyl alcohol, expand the application range of polyvinyl alcohol films, and extend the shelf life and sensory properties of food. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a rosmarinic acid and zinc ion double cross-linked PVA composite film and a preparation method and application thereof.
[0004] In a first aspect of the present invention, the present invention provides a method for preparing a rosmarinic acid and zinc ion double cross-linked PVA composite film. According to an embodiment of the present invention, the method comprises: (1) mixing rosmarinic acid and polyvinyl alcohol aqueous solution to react to obtain polyvinyl alcohol / rosmarinic acid initial solution; (2) dialyzing the polyvinyl alcohol / rosmarinic acid initial solution to obtain a polyvinyl alcohol / rosmarinic acid pure solution; (3) Mixing the polyvinyl alcohol / rosmarinic acid pure solution with zinc chloride solution to obtain polyvinyl alcohol / rosmarinic acid / Zn 2+ Solution; (4) the polyvinyl alcohol / rosmarinic acid / Zn 2+ The solution is dried to remove water, thereby obtaining a double cross-linked PVA composite film of rosmarinic acid and zinc ions.
[0005] According to the preparation method of the rosmarinic acid and zinc ion double cross-linked PVA composite film of the above embodiment of the present invention, first, rosmarinic acid and polyvinyl alcohol aqueous solution are mixed and reacted to obtain polyvinyl alcohol / rosmarinic acid initial solution, rosmarinic acid (RA) is a naturally occurring water-soluble phenolic compound, widely present in a variety of medicinal plants, and rosmarinic acid has a variety of biological activities, such as antibacterial and antioxidant activities. PVA is covalently coupled with rosmarinic acid at 120°C as a polymer to form a PVA / RA solution, which not only overcomes the problem of poor bioavailability of rosmarinic acid, but also significantly improves the antibacterial, antioxidant and anti-ultraviolet capabilities of polyvinyl alcohol film. The polyvinyl alcohol / rosmarinic acid initial solution is dialyzed to obtain a polyvinyl alcohol / rosmarinic acid pure solution, a small amount of unreacted rosmarinic acid is present in the polyvinyl alcohol / rosmarinic acid initial solution, and unreacted rosmarinic acid is removed by dialysis.
[0006] The inventors found that although rosmarinic acid modified polyvinyl alcohol can improve the antibacterial, antioxidant and UV resistance of polyvinyl alcohol film, polyvinyl alcohol / rosmarinic acid is a process in which hydroxyl and carboxyl groups are covalently coupled to form ester groups through esterification reaction, and the hydroxyl groups on polyvinyl alcohol are reduced, resulting in weakened mechanical properties of the film. Therefore, a pure polyvinyl alcohol / rosmarinic acid solution is mixed with a zinc chloride solution to obtain a polyvinyl alcohol / rosmarinic acid / Zn 2+ The solution can effectively improve the mechanical properties of the membrane by chelating covalent zinc ions to rosmarinic acid through metal chelation, and can also further improve the antibacterial properties of the membrane. 2+ The solution is dried to remove water, thereby obtaining a double cross-linked PVA composite film of rosmarinic acid and zinc ions.
[0007] In some embodiments of the present invention, in step (1), the mass ratio of rosmarinic acid to the polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 1:(5-200). For example, the mass ratio of rosmarinic acid to the polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 1:5, 1:10, 1:30, 1:50, 1:80, 1:100, 1:120, 1:140, 1:160, 1:180, 1:200, etc., or any range between the above two values. The inventors have found that controlling the mass ratio of rosmarinic acid to the polyvinyl alcohol in the polyvinyl alcohol aqueous solution within the above range can improve the antibacterial, antioxidant and UV resistance of the polyvinyl alcohol film.
[0008] In some embodiments of the present invention, the concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 80-120 g / L. For example, the concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 80 g / L, 83 g / L, 87 g / L, 90 g / L, 95 g / L, 100 g / L, 105 g / L, 110 g / L, 115 g / L, 120 g / L, etc., or the range between any two of the above values. The inventors have found that the concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is within the above range, which is conducive to better modification of polyvinyl alcohol by rosmarinic acid and improves the antibacterial, antioxidant and anti-ultraviolet capabilities of the polyvinyl alcohol film.
[0009] In some embodiments of the present invention, in step (1), the temperature of the mixed reaction is 110°C to 120°C, and the time is 2h to 4h. For example, the reaction temperature is 110°C, 112°C, 114°C, 116°C, 118°C, 120°C, etc., and the time is 2h, 2.5h, 3h, 3.2h, 3.5h, 3.7h, 4h, etc. When the temperature and time of the mixed reaction are within the above range, rosmarinic acid and polyvinyl alcohol can fully react, thereby increasing the yield of rosmarinic acid-modified polyvinyl alcohol.
[0010] In some embodiments of the present invention, in step (1), the preparation process of the polyvinyl alcohol aqueous solution comprises: mixing polyvinyl alcohol and water at 90° C. to 100° C. and reacting for 4 h to 6 h. Thus, the polyvinyl alcohol can be fully dissolved in the aqueous solution to prepare a polyvinyl alcohol aqueous solution of suitable concentration.
[0011] In some embodiments of the present invention, in step (2), the dialysis uses a dialysis bag with a molecular weight of 800-1000 and ultrapure water, thereby effectively removing unreacted rosmarinic acid.
[0012] In some embodiments of the present invention, in step (3), the concentration of zinc chloride in the solution after the pure solution of polyvinyl alcohol / rosmarinic acid and the zinc chloride solution are mixed is 0.8 g / L to 15 g / L. For example, the concentration is 0.8 g / L, 1.0 g / L, 2 g / L, 5 g / L, 7 g / L, 9 g / L, 12 g / L, 15 g / L, etc., or a range between any two of the above values. The inventors have found that controlling the concentration of zinc chloride in the mixed solution within the above range is conducive to the action of zinc ions on rosmarinic acid, and meets a certain amount of zinc ions, thereby improving the mechanical properties of the film.
[0013] In some embodiments of the present invention, in step (3), the concentration of the zinc chloride solution is 50 g / L to 300 g / L. For example, the concentration of the zinc chloride solution is 50 g / L, 80 g / L, 100 g / L, 200 g / L, 300 g / L, etc., or a range between any two of the above values.
[0014] In some embodiments of the present invention, in step (3), the mixing temperature is room temperature and the mixing time is 20 h to 25 h.
[0015] In some embodiments of the present invention, the preparation process of the zinc chloride solution includes: dissolving zinc chloride powder with 0.07-0.1 mol / L hydrochloric acid, shaking for 15-20 min, and standing for reaction for 20-30 h.
[0016] In some embodiments of the present invention, step (3) further comprises: mixing polyvinyl alcohol / rosmarinic acid / Zn 2+ The solution is dialyzed in a 0.01-0.07 mol / L hydrochloric acid solution for 20-32 hours to remove excess unreacted zinc ions.
[0017] In some embodiments of the present invention, in step (4), the drying temperature is 50°C to 60°C and the drying time is 24h to 32h. 2+ The moisture content of the solution and the stability of the prepared film are ensured.
[0018] It should be noted that those skilled in the art can change the polyvinyl alcohol / rosmarinic acid / Zn 2+ After the solution is placed in molds of different shapes, it is dried and dehydrated to obtain a rosmarinic acid and zinc ion double-crosslinked PVA composite film of a required shape.
[0019] In a second aspect of the present invention, the present invention provides a rosmarinic acid and zinc ion double cross-linked PVA composite film. According to an embodiment of the present invention, the rosmarinic acid and zinc ion double cross-linked PVA composite film is prepared by the above method. Thus, the rosmarinic acid and zinc ion double cross-linked PVA composite film has excellent antibacterial, antioxidant and anti-ultraviolet capabilities and good mechanical properties.
[0020] In the third aspect of the present invention, the present invention proposes the application of the above-mentioned rosmarinic acid and zinc ion double cross-linked PVA composite film in the field of food packaging.
[0021] The present invention has at least the following technical effects: (1) Based on the principle of esterification reaction, the carboxyl group of rosmarinic acid can be combined with the hydroxyl group of PVA at 120°C to form a PVA / RA conjugate to improve the antioxidant and UV resistance of the polyvinyl alcohol film. Zinc ions and RA are combined together through metal chelation to enhance the mechanical properties of the film and further improve the antibacterial properties of the PVA film. The rosmarinic acid and zinc ion double-crosslinked PVA composite film prepared by the present invention has excellent antibacterial, antioxidant and UV resistance capabilities as well as good mechanical properties.
[0022] (2) The method for preparing a double-crosslinked PVA composite film of rosmarinic acid and zinc ions of the present invention has a simple process, is easy to operate, has low equipment requirements, has readily available raw materials, is environmentally friendly, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 PVA / RA / Zn of Examples 1-5 2+ Physical picture of the solution; Figure 2 It is the ultraviolet absorption spectra of the solutions of Examples 1-5 and Comparative Examples 1 and 3; Figure 3 is a comparison chart of the zinc ion chelation amount of the solutions of Examples 1, 7-10; Figure 4It is the ATR-FTIR spectra of the solutions of Example 1 and Comparative Examples 1-3; Figure 5 It is a graph showing the UV-visible performance analysis results of the films of Example 1 and Comparative Examples 1-2; Figure 6 It is a graph showing the antibacterial performance test results of the solutions of Example 1 and Comparative Examples 1-2; Figure 7 1 is a graph showing the test results of the anti-oxidation performance of the films of Example 1 and Comparative Examples 1-2; Figure 8 It is a graph showing the mechanical properties test results of the films of Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0025] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0026] The experimental materials and instruments used in the following examples and comparative examples are: Polyvinyl alcohol (type 1799), AR, was purchased from Shanghai Titan Technology Co., Ltd.; Rosmarinic acid and zinc chloride (97%) were purchased from Aladdin; Anhydrous zinc chloride was purchased from Shanghai Maclean; The autoclave was purchased from Beijing Huotong Experimental Instrument Co., Ltd. Magnetic stirrer (Aika), RCT bask set; Vacuum drying oven (Linhai Yonghao), model DZF-6024; Rotary evaporator (Shanghai Yarong), model RE-52A; The three-speed handheld high-speed blender (Zhan Yi) was purchased from Beijing Yanqiwan Biotechnology Co., Ltd.; Plastic vacuum desiccator, model HP-PC-150, was purchased from Changde Beekman Biotechnology Co., Ltd.; UV spectrophotometer, model Q-6, was purchased from Shanghai Yuanxi Instrument Co., Ltd.
[0027] Example 1 (1) Take 20 ml of 100 g / L PVA aqueous solution in a beaker, weigh 163.6 mg of rosmarinic acid (mass ratio PVA: RA = 12.2:1) using a weighing instrument and put it into the beaker, stirring until dissolved.
[0028] (2) The solution was heated to 120°C and 300 rpm in an autoclave, and stirred for 2 h with a small rotor to achieve full cross-linking, thereby obtaining a fully cross-linked PVA / RA solution.
[0029] (3) Dialysis bag treatment method: Take 10g of sodium bicarbonate and 186mg of EDTA (ethylenediamine) and add them to 500ml of ultrapure water; put the dialysis bag in the above solution, start timing from boiling for 10 minutes; take out the dialysis bag and rinse it thoroughly with ultrapure water; put it in ultrapure water, start timing from boiling for 10 minutes; take out the dialysis bag and put it in a beaker of ultrapure water.
[0030] (4) The PVA / RA solution obtained in step (2) was dialyzed using a dialysis bag with a molecular weight of 1000. The solution was placed in ultrapure water and dialyzed for two days, with the ultrapure water being replaced three times a day (with stirring).
[0031] (5) Take 10 ml of the dialyzed PVA / RA solution, add 1.2 ml of 136 g / L ZnCl2 solution (weigh zinc chloride and put it into 0.07 mol / L dilute hydrochloric acid), the ZnCl2 concentration in the mixed solution is 14.6 g / L, stir thoroughly for 15 minutes, then put it into a centrifuge tube and cross-link at room temperature for 24 hours to obtain PVA / RA / Zn 2+ Then dialyze with 0.05 mol / l hydrochloric acid solution for 24 h.
[0032] (6) Take PVA / RA / Zn 2+ The solution was placed in a small acrylic mold and vacuumed to remove bubbles (close the air horizontally, open the vacuum clockwise, close the vacuum counterclockwise, and slowly open a small hole for air after the end). After removing the bubbles, it was directly poured into the mold, dried at 50°C for 24 h, and demolded to obtain a rosmarinic acid and zinc ion double-crosslinked PVA composite film.
[0033] Example 2 The difference between Example 2 and Example 1 is: In step (1) of Example 2, PVA:RA=6.1:1.
[0034] Example 3 The difference between Example 3 and Example 1 is: In step (1) of Example 3, PVA:RA=24.4:1.
[0035] Example 4 The difference between Example 4 and Example 1 is: In step (1) of Example 4, PVA:RA=48.8:1.
[0036] Example 5 The difference between Example 5 and Example 1 is: In step (1) of Example 5, PVA:RA=97.6:1.
[0037] Example 6 The difference between Example 6 and Example 1 is: In step (1) of Example 6, PVA:RA=195.2:1.
[0038] Example 7 The difference between Example 7 and Example 1 is: The ZnCl2 concentration in the mixed solution is 7.3 g / L.
[0039] Example 8 The difference between Example 8 and Example 1 is: The ZnCl2 concentration in the mixed solution is 3.65 g / L.
[0040] Example 9 The difference between Example 9 and Example 1 is as follows: The ZnCl2 concentration in the mixed solution is 1.83 g / L.
[0041] Example 10 The difference between Example 10 and Example 1 is: The ZnCl2 concentration in the mixed solution is 0.92 g / L.
[0042] Comparative Example 1 (1) Add 10.0 g of PVA to 100 ml of aqueous solution and heat by rotary evaporation at 95 °C for 2 h until the PVA is completely dissolved to obtain a PVA aqueous solution.
[0043] (2) Mix the PVA solution, shake and ultrasonicate it, and then evacuate it to remove bubbles. Finally, dry it at 60°C to obtain the polyvinyl alcohol material.
[0044] Comparative Example 2 (1) Take 20 ml of 100 g / L PVA aqueous solution in a beaker, weigh 163.6 mg of rosmarinic acid (mass ratio PVA: RA = 12.2:1) using a weighing instrument and put it into the beaker, stirring until dissolved.
[0045] (2) The solution was heated to 120°C and 300 rpm in an autoclave, and stirred for 2 h with a small rotor to achieve full cross-linking, thereby obtaining a fully cross-linked PVA / RA solution.
[0046] (3) Dialysis bag treatment method: Take 10g of sodium bicarbonate and 186mg of EDTA (ethylenediamine) and add them to 500ml of ultrapure water; put the dialysis bag in the above solution, start timing from boiling for 10 minutes; take out the dialysis bag and rinse it thoroughly with ultrapure water; put it in ultrapure water, start timing from boiling for 10 minutes; take out the dialysis bag and put it in a beaker of ultrapure water.
[0047] (4) The PVA / RA solution obtained in step (2) was dialyzed using a dialysis bag with a molecular weight of 1000. The solution was placed in ultrapure water and dialyzed for two days, with the ultrapure water being replaced three times a day (with stirring).
[0048] (5) Place the dialyzed PVA / RA solution in a small acrylic mold and evacuate the solution to remove bubbles (turn off the air horizontally, turn on the vacuum clockwise, turn off the vacuum counterclockwise, and slowly open a small hole for air after the air bubbles are removed). Pour the solution directly into the mold and dry it at 50 °C for 24 h. De-mold the solution to obtain a double-crosslinked PVA composite film of rosmarinic acid and zinc ions.
[0049] Comparative Example 3 Take 20 ml of 100 g / L PVA aqueous solution in a beaker, weigh 163.6 mg of rosmarinic acid (mass ratio PVA: RA = 12.2:1) with a weighing instrument and put it into the beaker, stir until dissolved to obtain a PVA+RA solution.
[0050] The product properties of Examples 1-10 and Comparative Examples 1-3 were tested.
[0051] (1) The actual pictures of the PVA / RA solutions of Examples 1-5 are as follows: Figure 1 As shown, from Figure 1 It can be seen that as the amount of RA added increases, the color of the solution gradually changes from light yellow to dark yellow, and finally becomes turbid. The reason why Example 2 is turbid is that the increase in the content of rosmarinic acid leads to a decrease in the hydroxyl group of PVA, an increase in hydrophobicity, and a portion of PVA is precipitated, and the solution becomes turbid.
[0052] (2) The ultraviolet absorption spectra of the PVA / RA solutions of Examples 1-5, the PVA aqueous solution of Comparative Example 1, and the PVA+RA solution of Comparative Example 3 are shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that the solution of Example 1 has the highest ultraviolet absorbance. The solution of Comparative Example 1 has the worst ultraviolet absorbance. As the amount of RA added decreases, the ultraviolet absorbance of the solution also decreases. The solution of Example 1 shows the highest absorbance, and there is not much difference from the simple mixed PVA+RA solution (Comparative Example 3), indicating that the experimental treatment method does not affect the performance of rosmarinic acid.
[0053] (3) Comparison of the amount of zinc ion chelated in the solutions of Examples 1, 7-10 is shown in the figure below: Figure 3 As shown. Since the zinc ion is chelated by the two phenolic hydroxyl groups on rosmarinic acid, the content of the added zinc ion will have a saturated value. The comparison of the zinc ion chelation amount of the solution of Examples 1 / 7-10 is shown in Figure 3 As shown, from Figure 3 It can be seen that when the zinc ion content is 163.2 mg, the chelating amount reaches the saturation value.
[0054] (4) The ATR-FTIR spectra of the solutions of Example 1 and Comparative Examples 1-3 are as follows: Figure 4 As shown, from Figure 4 Yes, the characteristic absorption peaks of PVA in Comparative Example 1 are 3340 cm −1 (OH stretching), 2940 cm −1 (hydrocarbon CH stretching), 1426 cm −1 (CH2 bending vibration) and 1084 cm −1 (CO stretching). Compared with PVA, PVA / RA of Comparative Example 2 has a −1 The absorption peak at 53.47 and 531.32 was enhanced, indicating that the CO content increased. This indicates that an esterification cross-linking reaction occurred between the hydroxyl group of polyvinyl alcohol and the carboxyl group of rosmarinic acid to form an ester group. The C-OH peak of the PVA+RA solution of Comparative Example 3 shifted to 532.52 eV. At the same time, new peaks appeared at 533.47 and 531.32, which were attributed to C=O and -COO-. The PVA / RA / Zn solution of Example 1 2+ 1265 cm in the spectrum −1 The strong peak at 1259 cm in the PVA / RA spectrum corresponds to −1 The vibration of the CO group of catechol and the change of its chemical shift suggest that the catechol structure in PVA / RA may be the site of metal ion coordination, which indicates that the phenolic hydroxyl group in RA is involved in metal chelation.
[0055] (5) The UV-visible performance analysis of the films of Example 1 and Comparative Examples 1-2 is as follows: Figure 5 As shown, from Figure 5 It can be seen that PVA alone does not show any significant UV protection, as evidenced by the 85-90% transmittance in the UV region. On the other hand, the composite films of Example 1 and Comparative Example 2 show extensive and significant UV absorption (protection) and high visible light transmittance.
[0056] (6) Example 1, Comparative Example 1-2 Solution antibacterial performance test, the specific process is as follows: LB (TSA) liquid culture medium, LB Escherichia coli (TSA Staphylococcus aureus) liquid culture medium for liquid culture test, according to the number of colonies in the culture medium to determine the antibacterial effect of the liquid, the fewer the number of colonies, the stronger the antibacterial effect. The antibacterial performance test results are as follows Figure 6 As shown, from Figure 6 It can be seen that by testing PVA (Comparative Example 1), PVA / RA (Comparative Example 2) and PVA / RA / Zn 2+ (Example 1) The number of strains in the solution was found to be PVA / RA and PVA / RA / Zn 2+ The number of bacterial beads in the PVA / RA / Zn film decreased compared with the blank control and pure PVA, and the antibacterial effect was good, indicating that the composite film has good antibacterial properties. 2+ Compared with PVA / RA solution, the antibacterial effect of the solution is significantly improved.
[0057] (7) Example 1, Comparative Example 1-2 Film antioxidant performance test, the specific process is as follows: add the solution to the DPPH solution, and test the absorbance of DPPH after 30-40 minutes. The lower the absorbance, the stronger the antioxidant property. The test results are as follows: Figure 7 As shown, from Figure 7 It can be seen that PVA, PVA / RA and PVA / RA / Zn 2+ The DPPH scavenging rate of PVA / RA and PVA / RA / Zn 2+ The solution has good free radical scavenging ability and good antioxidant effect, indicating that the film of the present application has good antioxidant properties.
[0058] (8) Mechanical property test of the film of Example 1 and Comparative Example 2. The specific process is as follows: the film is cut into strips with a width of 1-4 cm and a length of 2-4 cm for mechanical property test. The four indicators of tensile strength, elongation at break, elastic modulus and tensile stress at break are tested. The film is 20 mm min -1 The strain rate was set to 0.05 and the test results were shown in Table 1. Figure 8 ,from Figure 8 It can be seen that the tensile strength, elongation at break, modulus and tensile stress at break of PVA film are 47MPa, 151%, 2080.76645MPa and 4.0823MPa respectively; the tensile strength, elongation at break, modulus and tensile stress at break of PVA / RA film are 36MPa, 93%, 1781.0437MPa and 3.40915MPa respectively; 2+The tensile strength, elongation at break, modulus and tensile stress at break of the film are 67MPa, 266%, 2534.2522MPa and 6.4344MPa respectively. 2+ The tensile strength of the film increased by 29.85MPa compared with that of PVA film and 46.27MPa compared with that of PVA / RA film; 2+ The elongation at break of the film increased by 65.04% compared with that of the PVA film and by 42.23% compared with that of the PVA / RA film, which indicates that the addition of zinc ions can greatly improve the decrease in the mechanical properties of the PVA film caused by the addition of rosmarinic acid. Figure 8 It can be seen that PVA / RA / Zn 2+ It shows strong tensile strength, elongation at break, elastic modulus and tensile stress at break.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a double cross-linked PVA composite film of rosmarinic acid and zinc ions, characterized in that: include: (1) mixing rosmarinic acid and polyvinyl alcohol aqueous solution to react to obtain polyvinyl alcohol / rosmarinic acid initial solution; (2) dialyzing the polyvinyl alcohol / rosmarinic acid initial solution to obtain a polyvinyl alcohol / rosmarinic acid pure solution; (3) Mixing the polyvinyl alcohol / rosmarinic acid pure solution with zinc chloride solution to obtain polyvinyl alcohol / rosmarinic acid / Zn 2+ Solution; (4) the polyvinyl alcohol / rosmarinic acid / Zn 2+ The solution is dried to remove water, thereby obtaining a double cross-linked PVA composite film of rosmarinic acid and zinc ions.
2. The method according to claim 1, characterized in that: In step (1), the mass ratio of rosmarinic acid to polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 1:(5-200); And / or, the concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 80-120 g / L; And / or, the temperature of the mixed reaction is 110° C. to 120° C., and the time is 2 h to 4 h.
3. The method according to claim 1 or 2, characterized in that: In step (1), the preparation process of the polyvinyl alcohol aqueous solution includes: mixing polyvinyl alcohol and water and reacting them at 90° C. to 100° C. for 4 h to 6 h.
4. The method according to claim 1, characterized in that: In step (2), the dialysis uses a dialysis bag with a molecular weight of 800-1000 and ultrapure water.
5. The method according to claim 1, characterized in that: In step (3), the concentration of zinc chloride in the solution after the pure polyvinyl alcohol / rosmarinic acid solution is mixed with the zinc chloride solution is 0.8 g / L to 15 g / L; And / or, the concentration of the zinc chloride solution is 50 g / L to 300 g / L; And / or, the mixing temperature is room temperature, and the mixing time is 20h~25h.
6. The method according to claim 1 or 5, characterized in that: The preparation process of the zinc chloride solution comprises: dissolving zinc chloride powder with 0.07-0.1 mol / L hydrochloric acid, shaking for 15-20 minutes, and standing for reaction for 20-30 hours.
7. The method according to claim 1 or 5, characterized in that: Step (3) further comprises: mixing polyvinyl alcohol / rosmarinic acid / Zn 2+ The solution was dialyzed in 0.01~0.07mol / L hydrochloric acid solution for 20h~32h.
8. The method according to claim 1, characterized in that: In step (4), the drying temperature is 50°C to 60°C and the drying time is 24h to 32h.
9. A double cross-linked PVA composite film of rosmarinic acid and zinc ions, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. Application of the double cross-linked PVA composite film of rosmarinic acid and zinc ions according to claim 9 in the field of food packaging.
Citation Information
Patent Citations
Grape preservative paper and manufacturing method thereof
CN103469679A
Natural environment-friendly preservative, preparation method and meat quality environment-friendly preservative film
CN109793039A
Composite hydrogel material loaded with rosmarinic acid and preparation method and application of composite hydrogel material
CN110742859A
Preparation method of zinc ion hydrophilic metal organic framework blended polyvinyl alcohol composite membrane
CN118105851A
Film and method for producing film
JP2021014533A
Cited By
Environment-friendly heat stabilizer as well as preparation method and application thereof
CN120554860A